Decorating InSe Surface by Gold Species for Improved Carrier Transport and Efficient Sunlight Harvesting Toward High‐Performance Flexible Photodetectors. Issue 2 (22nd November 2022) - Li, Zhongjun; Qiao, Hui; Liu, Fei; Zhou, Yang; Zhang, Yuan; Wang, Yachao; Xu, Feicui; Huang, Guoyi; Yue, Shiqin; Liu, Wenlan; Zhao, Huafu; Tan, Hui; et al.
Abstract: Two‐dimensional (2D) materials have aroused widespread interest due to the high potential in modern photoelectronics. The strategy for improving the stability of 2D materials in the air, reinforcing formation, and transport of photoexcited carriers would open up promising routes toward flexible facilities. In this paper, surface engineering is executed on 2D InSe by decorating Au species for a lower bandgap allowing for efficient sunlight harvesting and decreased barrier with the substrate for improved electron transport. Moreover, hot electrons produced by Au nanoparticles under light irradiation pour into InSe for boosting photocurrent. Au nanoparticles also serve as conducting bridges in InSe−Au photoanode, where the contact resistance is two orders of magnitude lower than that of InSe electrode. Compared with InSe and other 2D counterparts, InSe−Au flexible photoelectrochemical detectors behave with outstanding performances under sunlight irradiation, including responsibility 55.4 µA W −1, detectivity 4.18 × 10 9 Jones. Importantly, the working electrode shows excellent ON/OFF switching stability after bending for 5000 times (3 months of storage in the air). This surface engineering provides a general strategy to tailor 2D materials for wearable photoelectronic devices in the future. Abstract : InSe nanosheets decorated by Au nanoparticles exhibit efficient sunlight absorption compared to the pristine InSe. The improved photoelectric response of the InSe−Au hybrid is contributed by surface plasmon resonance of Au nanoparticles and tailored band structure, making the hybrid a candidate for flexible photoelectric devices.